d-wave bond-order charge excitations in electron-doped cuprates - Yamase, Hiroyuki (2015)
We study charge excitation spectra in the two-dimensional t-J model on a square lattice to explore a charge-order tendency recently found in electron-doped cuprates around the carrier density 0.15. The static susceptibility of d-wave charge density, which corresponds to the nematic susceptibility at the momentum transfer q = (0, 0), shows two characteristic peaks at momenta of the form q1 = (q , q ) and q2 = (q, 0). These two peaks originate from the so-called 2kF scattering processes enhanced by the d-wave character of the bond-charge density. The peak at q1 is much broader, but develops to be very sharp in the vicinity of its instability, whereas the peak at q2 becomes sharper with decreasing temperature, but does not diverge. The equaltime correlation function, which is measured by resonant x-ray scattering, exhibits a momentum dependence similar to the static susceptibility. We also present energy-resolved charge excitation spectra. The spectra show a V-shaped structure around q = (0, 0) and bend back toward closeto-zero energy due to the charge-order tendency at q1 and q2. The resulting spectra form gap-like features with a maximal gap at q ≈ q1/2 and q2/2. We discuss implications for the recent experiments in electron-doped cuprates.